Pendampingan Baca Tulis Al-Qur’an Menggunakan Metode Fatullah di Pondok Tahfizh Tazkiyah - Nurhapipah, Nurhapipah; Kustati, Martin; Gusmirawati, Gusmirawati (Al-DYAS, 2023)
The high interest of parents in directing children to study the Qur'an means that there needs to be important attention for a tahfizh teacher to teach the Qur'an comprehensively and continuously. with the applicable tajwid rules, special attention is needed from the tahfzih teacher to always upgrade learning so that learning in class is more active and innovative. So that a new method of learning is formed so that the students become more proficient in learning the Alquran. Because of the reality that occurs in the field, students find it difficult to understand the meaning and nature of letters correctly. There is also boredom among students in studying due to the long practice of reciting recitation material in the Alquran. The method that the author uses is the Participatory Action Research (PAR) approach, where this research is oriented towards empowerment and change in society. It is clear that this writing is oriented towards quality change. Based on the results and assistance above, it can be concluded that assistance in reading and writing the Alquran through the Fatullah Method at Pondok Tahfizh Tazkiyah has been carried out well and can indirectly improve the reading and writing skills of the Alquran for the students of Pondok Tahfizh Tazkiyah.